Tracking pollution from fur farms using forensic paleolimnology - Kissinger, Jennifer; Gregory, Braden; Clarkson, Chloe; Libera, Nell; Eickmeyer, David; Kimpe, Linda; Kurek, Josh; Smol, John; Blais, Jules (Université d'Ottawa | University of Ottawa, 2023)
Eutrophication, which remains one of the greatest threats to water quality worldwide, is particularly acute in agricultural areas. Here we assessed long-term drivers of potential pollution inputs to lakes in southwest Nova Scotia (Canada), a region marked by fur farming (mainly mink) and other agricultural activities. We used a BACI (before-after-control-impact) study design with sediment cores collected from 14 lakes selected based on their proximity to mink farms. We combined economic data, mink faecal samples, and a series of geochemical markers in dated sediment cores, including sterols, δ15N, visible reflectance spectroscopy (VRS)-inferred chlorophyll-a, and heavy metals, to relate changes in sediment geochemistry to the growth of mink farms in the region. Sterol biomarkers (cholesterol and -sitosterol) measured in a range of samples (i.e. mink faeces and feed, aquaculture feed), were elevated where mink farms were located close to each study lake. Mink-related sterols (cholesterol, -sitoserol), δ15N measurements, VRS chlorophyll-a, and heavy metals As, Cu, Sr increased in the 1980s coeval with a ~400% increase of mink farms in the region, especially near Nowlans Lake. Agricultural impacts were subtler in other lakes. Our study expands on prior applications of geochemical fingerprinting in forensic paleolimnology when direct monitoring data are incomplete. This multi-proxy approach has promising applications for environmental pollution assessments in other lake ecosystems experiencing water quality issues.
Keywords: paleolimnology; contaminants; mink; lakes; eutrophication; sterols; stable isotopes